Non-self mutation: double-stranded RNA elicits antiviral pathogenic response in a Drosophila model of expanded CAG repeat neurodegenerative diseases. (9th May 2019) - Eyk, Clare L van; Samaraweera, Saumya E; Scott, Andrew; Webber, Dani L; Harvey, David P; Mecinger, Olivia; O'Keefe, Louise V; Cropley, Jennifer E; Young, Paul; Ho, Joshua; Suter, Catherine; Richards, Robert I
Abstract: Inflammation is activated prior to symptoms in neurodegenerative diseases, providing a plausible pathogenic mechanism. Indeed, genetic and pharmacological ablation studies in animal models of several neurodegenerative diseases demonstrate that inflammation is required for pathology. However, while there is growing evidence that inflammation-mediated pathology may be the common mechanism underlying neurodegenerative diseases, including those due to dominantly inherited expanded repeats, the proximal causal agent is unknown. Expanded CAG.CUG repeat double-stranded RNA causes inflammation-mediated pathology when expressed in Drosophila . Repeat dsRNA is recognized by Dicer-2 as a foreign or 'non-self' molecule triggering both antiviral RNA and RNAi pathways. Neither of the RNAi pathway cofactors R2D2 nor loquacious are necessary, indicating antiviral RNA activation. RNA modification enables avoidance of recognition as 'non-self' by the innate inflammatory surveillance system. Human ADAR1 edits RNA conferring 'self' status and when co-expressed with expanded CAG.CUG dsRNA in Drosophila the pathology is lost. Cricket Paralysis Virus protein CrPV-1A is a known antagonist of Argonaute-2 in Drosophila antiviral defense. CrPV-1A co-expression also rescues pathogenesis, confirming anti-viral-RNA response. Repeat expansion mutation therefore confers 'non-self' recognition of endogenous RNA, thereby providing a proximal, autoinflammatory trigger for expanded repeat neurodegenerative diseases.